TETO VERDE COMO ESTRATÉGIA BIOCLIMÁTICA PARA O SEMIÁRIDO ALAGOANO - Silva, Wellington Souza; Barbosa, Ricardo Víctor Rodrigues (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The green roofs have been widely used around the world, presenting itself as an alternative to attenuate the internal temperature of the buildings, reduce the effects of heat island and other benefits. The system consists of a waterproof structure (slab), a layer of draining material superimposed by a geo-textile filter, substrate (soil) and vegetation. The objective of this work was to propose a green roof system adapted to the climatic reality of the Alagoan semi-arid region, more specifically in the city of Arapiraca, where the thermal inertia is indicated by the Bioclimatic Chart of Givoni as a constructive strategy for the city. For this purpose, a bibliographical review will be carried out on the theme, mainly addressing techniques and materials appropriate to the climate in question. The investigations indicated that the green roof system molded in situ, using liquid waterproofing, drainage with expanded clay or crushed brick, filtering with bidim blanket and prepared soil substrate is the indicated green roof composition for the city of Arapiraca-AL, with two species of plants possible for application: Arachis repens Handro (grama-amendoim) and Richardia grandiflora (poaia-rasteira).